Chicken (Gallus gallus) endogenous retrovirus generates genomic variations in the chicken genome. Issue 1 (December 2017) - Lee, Jinmin; Mun, Seyoung; Kim, Dong; Cho, Chun-Sung; Oh, Dong-Yep; Han, Kyudong
Abstract Background Transposable elements (TEs) comprise 10% of the chicken (Gallus gallus ) genome. The content of TEs is much lower than that of mammalian genomes, where TEs comprise around half of the genome. Endogenous retroviruses are responsible for 1.3% of the chicken genome. Among them isGallus gallus endogenous retrovirus 10 (GGERV10), one of the youngest endogenous retrovirus families, which emerged in the chicken genome around 3 million years ago. Results We identified a total of 593 GGERV10 elements in the chicken reference genome using UCSC genome database and RepeatMasker. While most of the elements were truncated, 49 GGERV10 elements were full-length retaining 5′ and 3′ LTRs. We examined in detail their structural features, chromosomal distribution, genomic environment, and phylogenetic relationships. We compared LTR sequence among five different GGERV10 subfamilies and found sequence variations among the LTRs. Using a traditional PCR assay, we examined a polymorphism rate of the 49 full-length GGERV10 elements in three different chicken populations of the Korean domestic chicken, Leghorn, andAraucana . The result found a breed-specific GGERV10B insertion locus in the Korean domestic chicken, which could be used as a Korean domestic chicken-specific marker. Conclusions GGERV10 family is the youngest ERV family and thus might have contributed to recent genomic variations in different chicken populations. The result of this study showed that one of GGERV10 elements integrated into the chicken genome after the divergence of Korean domestic chicken from other closely related chicken populations, suggesting that GGERV10 could be served as a molecular marker for chicken breed identification.